From Domestic Application to ICC: Analysing the Integration of ‘Restorative Justice’ in International Criminal Law - Chakrabarty, Saheli; Banerjee, Nirbindu (Kathmandu School of Law Review, 2025)
Restorative Justice ideology has emerged in the last three decades as a process indistinguishable from our justice systems’ humane identity. Reliability, healing, and community involvement are the cornerstones of restorative justice, which provides an alternative to conventional punitive justice systems. Applying this versatile process has not only improved the idea of justice in terms of criminal cases but has also led to the restoration of environments in many other settings where ‘justice’ might not be involved in the literal sense. The flexibility and flow of restorative justice ideology are thus essential parts of modern criminal justice and are signs of a paradigm shift. This paper thoroughly examines the conceptual flexibility of restorative justice and its implementation in diverse cultural settings, highlighting different models that adapt to the cultural and social milieu. Thereon, the paper analyses the convergence of this principle of justice outside national borders into international legal frameworks. Lastly, the paper, in its fundamental quest of analysing the ‘Restorative Justice’ models that have been metamorphosised by diverse municipal laws in the realm of International Criminal Law. The paper critically investigates the possibility of successfully integrating restorative justice, which has traditionally been used in national contexts, into the international criminal justice system, especially in the International Criminal Court (ICC).